Calcium-based nanostructures : transition between nanowires and inverted structures. - Teguh Asmara. (2009)
Compared to other metal-oxide-based nanowires which have been studied, CaO-based nanostructures remain largely unexplored. This is a pity, because CaO actually has many interesting properties that can be used for scientific and industrial purposes, especially the recent theoretical prediction of its extraordinary ferromagnetic properties. In this work, we have attempted to synthesize and characterized CaO-based nanowires grown by thermal vapor transport method. Along the road, it was found that when the growth parameters of the nanowires were slightly altered, totally different class of nanostructures called the inverted structures were unexpectedly formed on the substrate, which implied that there is some kind of transition between these two structures. Thus, it prompted us to study this transition by systematically varying the parameters that influence the growth of the nanostructures.